Age and extent of the Scandinavian ice sheet in northwest Russia. - Larsen, Eiliv; Lyså, Astrid; Demidov, Igor; Funder, Svend; Houmark-Nielsen, Michael; Kjær, Kurt Henrik; Murray, Andrew Sean (PANGAEA, 1999)
The last glacial maximum (LGM) of the Scandinavian ice sheet in the Arkhangelsk region has been identified morphologically as ridges and hummocks in an otherwise flat topography. Stratigraphically the limit is marked by the presence of till above Mikhulinian (last interglacial) sediments inside the ridges and by the absence of till outside the ridges. During the LGM, ice flowed into the region from the north and northwest forming a lobe in the Dvina--Vaga depression. The continuation northward, northeast of Arkhangelsk, is still somewhat uncertain, but evidence suggests that the outer margin of the Scandinavian ice sheet was situated in the Mezen drainage basin. Luminescence and radiocarbon dates suggest that the maximum position was attained after some 17 ka ago, and that deglaciation started close to 15 ka ago. This age for the maximum position is younger than the maximum position in the western peripheral areas of the Scandinavian ice sheet. This may be accounted for by initial ice build-up in the west followed by a successive migration of the ice divide(s) to the east as ice growth continued. Deglaciation was either by lateral retreat or isolation of dead ice masses causing areal downwasting.
Age determinations from northwest Russia
Keywords: Bobrovo; Chelmokhta; Koleshka; OUTCROP; Outcrop sample; Pasva; Psaryovo; Quaternary Environment of the Eurasian North; QUEEN; QUEEN_Exped; Raibola; Smotrakovka; Trepyzovo